The Role of Lectin Receptors and Their Ligands in Controlling Allergic Inflammation - Peters, Karin; Peters, Marcus (Frontiers in Immunology, 2021)
More than fifty c-type lectin receptors (CLR) are known and have been identified so far. Moreover, we know the group of galectins and sialic acid-binding immunoglobulin-type lectins that also belong to the carbohydrate-binding receptors of the immune system. Thus, the lectin receptors form the largest receptor family among the pathogen recognition receptors. Similar to the toll-like receptors (TLRs), the CLR do not only recognize foreign but also endogenous molecules. In contrast to TLRs, which have a predominantly activating effect on the immune system, lectin receptors also mediate inhibitory signals. They play an important role in innate and adaptive immunity for the induction, regulation and shaping of the immune response. The hygiene hypothesis links enhanced infection to protection from allergic disease. Yet, the microbial substances that are responsible for mediating this allergy-protective activity still have to be identified. Microbes contain both ligands binding to TLRs and carbohydrates that are recognized by CLR and other lectin receptors. In the current literature, the CLR are often recognized as the ‘bad guys’ in allergic inflammation, because some glycoepitopes of allergens have been shown to bind to CLR, facilitating their uptake and presentation. On the other hand, there are many reports revealing that sugar moieties are involved in immune regulation. In this review, we will summarize what is known about the role of carbohydrate interaction with c-type lectins and other sugar-recognizing receptors in anti-inflammation, with a special focus on the regulation of the allergic immune response.